1975
DOI: 10.1002/jss.400030102
|View full text |Cite
|
Sign up to set email alerts
|

On the physiological functions of teichoic acids

Abstract: The choline-containing teichoic acids of pneumococci can be modified by biosynthetic replacement of the choline residues with certain structural analogues, such as ethanolamine (EA) or the N-monomethyl-(MEA) and N-dimethyl-(DEA) amino derivatives of ethanolamine. Cells containing such analogues in their teichoic acids develop pleiomorphic alterations in several physiological properties, which include resistance to detergent-induced lysis and inhibition of cell separation (chain formation). We report here the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 11 publications
(8 reference statements)
4
36
0
Order By: Relevance
“…Pneumococci display an unusual surface molecule, phosphocholine, on the cell wall teichoic acid and the membranebound lipoteichoic acid (154). Studies have shown that PspA attaches itself to S. pneumoniae by noncovalent binding to the choline of both lipoteichoic and teichoic acids via its C-terminal end, consisting of the repeat region, also called the choline binding region (CBR) (Fig.…”
Section: Attachment To the Surface Of S Pneumoniaementioning
confidence: 99%
“…Pneumococci display an unusual surface molecule, phosphocholine, on the cell wall teichoic acid and the membranebound lipoteichoic acid (154). Studies have shown that PspA attaches itself to S. pneumoniae by noncovalent binding to the choline of both lipoteichoic and teichoic acids via its C-terminal end, consisting of the repeat region, also called the choline binding region (CBR) (Fig.…”
Section: Attachment To the Surface Of S Pneumoniaementioning
confidence: 99%
“…The ethanolamine-containing cell wall (R6EA) was prepared by an identical procedure, except that choline was replaced by 20 渭g/ml ethanolamine (Sigma-Aldrich) in the growth medium (49).…”
Section: Figurementioning
confidence: 99%
“…Since previous examinations of wall turnover in pneumococci had utilized either [3H]choline-labelled teichoic acid or peptidoglycan labelled with either ['4C]glutamic acid or [14C]lysine during growth in ethanolamine-containing medium [IS,16a], it was necessary to establish that lysine-labelled peptidoglycan synthesized in the usual choline-containing medium was also conserved and that release of cell wall label did not complicate the interpretation of peptidoglycan synthesis experiments. Exponential phase cultures of wild type, autolysis prone R 6 and the autolysis deficient strain lyt 4-4 were pulse labeled (3 min) with [3H]lysine (1 pCi/ml, 0.19 ng/ ml) and subsequently grown with an excess of unlabelled lysine (225 pg/ml) added immediately after the pulse.…”
Section: Analysis Of Pep T Idogly Can T Urno Ver During Growthmentioning
confidence: 99%